2014
DOI: 10.1161/atvbaha.113.302281
|View full text |Cite
|
Sign up to set email alerts
|

N ε -(Carboxymethyl)lysine-Receptor for Advanced Glycation End Product Axis Is a Key Modulator of Obesity-Induced Dysregulation of Adipokine Expression and Insulin Resistance

Abstract: Objective-Dysregulation of inflammatory adipokines by the adipose tissue plays an important role in obesity-associated insulin resistance. Pathways leading to this dysregulation remain largely unknown. We hypothesized that the receptor for advanced glycation end products (RAGE) and the ligand N ε -(carboxymethyl)lysine (CML) are increased in adipose tissue and, moreover, that activation of the CML-RAGE axis plays an important role in obesity-associated inflammation and insulin resistance. Approach and Results-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
187
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 35 publications
12
187
4
2
Order By: Relevance
“…Other studies found the same relationship and specifically confirmed the presence of CML in adipose tissue 17,18 . Taken together, it appears that CML is preferentially deposited in fat tissue and acts as an important mechanism involved in the dysregulation of adipokines in obesity, thereby contributing to the development of obesity-associated insulin resistance.…”
Section: Relationship Between Mid-gestational CML Glucose Indices Ansupporting
confidence: 62%
“…Other studies found the same relationship and specifically confirmed the presence of CML in adipose tissue 17,18 . Taken together, it appears that CML is preferentially deposited in fat tissue and acts as an important mechanism involved in the dysregulation of adipokines in obesity, thereby contributing to the development of obesity-associated insulin resistance.…”
Section: Relationship Between Mid-gestational CML Glucose Indices Ansupporting
confidence: 62%
“…First, the high-temperature and long-time cooking of foods can generate AGEs that are exogenously introduced with the diet [46]. Second, emerging evidence indicates that high dietary simple sugars consumption can represent a substantial source of endogenous AGEs [47]. In this regards, it is a long time that studies started to investigate the glycative potential of different monosaccharides by in vitro incubations with physiologically relevant proteins such as haemoglobin and serum albumin [48,49].…”
Section: Glycation In Vitro Of Different Sugarsmentioning
confidence: 99%
“…This was in reasonable agreement with data described in literature [36][37][38][39][40][41] . The described method is suitable for studying AGEs in several different human and animal studies [42][43][44][45][46][47][48][49] and is a strong tool to investigate the putative effects of AGEs in the pathophysiology of different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Possible lifestyle interventions, such as glucose-, blood-pressure-and lipid-lowering treatments 50,53,54 and changes in dietary AGEs (due to diet interventions), may potentially influence circulating AGEs. Moreover, CML has been found to be trapped in adipose tissues 42,55 and consequently, plasma CML levels are lower in individuals with overweight compared to lean individuals 55 . Given the high prevalence of overweight and obesity in patients with T2DM, this phenomenon manifests more often in T2DM as compared to T1DM or lean individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation